The role of hybrid strategy in the innovation strategy process - R.V. (Економіка, управління та адміністрування)
The role of hybrid strategy in the process of innovative strategizing is considered. It is determined that a clean strategy does not lead to excellent results and is widely criticized. Scientists say that there has been a shift in focus from pure strategy to hybrid (integration of a set of strategies). This transformation is constantly growing. Therefore, from now on, a hybrid strategy based on the strategies of miles, snow and Porter is a vital concept for successful work in the context of innovative strategizing. The study discussed the benefits of using hybrid strategies. The results showed that such strategies are superior to Pure Strategies. Using hybrid strategies leads to increased market share, quality, flexibility, innovation, delivery time, and lower costs across sectors. On the other hand, literature analysis has shown that readiness for strategic change and response to strategic change pose the most notable challenges for adopting hybrid strategies. In addition, an overview of the current state of theoretical and practical implications for hybrid strategies was provided. Thus, a hybrid strategy based on Miles and snow encourages scientists to learn about strategic diversity.